DENSITAS TUMPARA (Tarsius tumpara) PADA HUTAN LINDUNG DAN HUTAN PRODUKSI DI PULAU SIAU SULAWESI UTARA - Bryan M. Kuheba; Jhony S. Tasirin; Maria Y. M. A. Sumakud; Saroyo Sumarto (Universitas Sam Ratulangi, 2015)
ABSTRACT The purpose of this study is to evaluate tumpara’s population and compare its density in each production forest and protected forests at Mount Tamata Siau Island. This study was conducted for one month in March 2014 at 7 plots in each forest type. Tumpara’s density and frequency was performed using sampling method and analized using descriptive statistics. Sightings density and frequency between production forests and protected forests then compared. Area description uses Importance Value Index (IVI). Correlation and simple regression analysis is used to see the relationship between vegetation and tumpara’s sightings frequency. Total basal area of the plots and shrub cover is used to evaluate tumpara’s sightings frequency. The results showed that the protected forest has tumpara density of 3.29 individuals/ha and 0.86 groups/ha while production forests has tumpara density of 2.14 individuals/ha and 0.47 groups/ha. Discovery frequency of tumpara in protected forest is 1.64 (0.02 to 3.26) times/day and the production forest has discovery frequency of 1.07 (0.21 to 1.93) times/day. There is a relation between vegetation cover and tumpara’s presence. The more area shrub covers, the higher tumpara population will be. Tumpara is more commonly seen in habitats dominated by Pandanus sp. Tumpara couldn’t be found in Myrstica fragrans dominated habitats.Keywords: Density, Sightings Frequency, Habitat, Tarsius tumpara, Siau Island